Reconstructive Surgery of the Aortic Valve in Children – Immediate Results - S. V. Varbanets (Ukrainian Journal of Cardiovascular Surgery, 2016)
The paper presents the analysis of the results of different methods of reconstructive surgery of the aortic valve and the aortic valve bivalve role as a predictor of reconstructive surgery.